2008
DOI: 10.1158/1535-7163.mct-08-0021
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNA-451 in resistance of the MCF-7 breast cancer cells to chemotherapeutic drug doxorubicin

Abstract: Many chemotherapy regiments are successfully used to treat breast cancer; however, often breast cancer cells develop drug resistance that usually leads to a relapse and worsening of prognosis. We have shown recently that epigenetic changes such as DNA methylation and histone modifications play an important role in breast cancer cell resistance to chemotherapeutic agents.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
446
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(473 citation statements)
references
References 49 publications
11
446
2
3
Order By: Relevance
“…Causes of cancer-specific drug resistance are currently believed to be linked to the random drug-induced mutational events (genetic hypothesis) and the druginduced nonmutational alterations of gene function (epigenetic hypothesis). Despite advances in the fields of resistance-associated molecular mechanisms, however, the underlying mechanisms of acquisition of resistance to chemotherapeutic agents are still poorly understood (Kovalchuk et al, 2008). Therefore, it should be acknowledged that other avenues must be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Causes of cancer-specific drug resistance are currently believed to be linked to the random drug-induced mutational events (genetic hypothesis) and the druginduced nonmutational alterations of gene function (epigenetic hypothesis). Despite advances in the fields of resistance-associated molecular mechanisms, however, the underlying mechanisms of acquisition of resistance to chemotherapeutic agents are still poorly understood (Kovalchuk et al, 2008). Therefore, it should be acknowledged that other avenues must be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, extensive studies have indicated the existence and importance of another mechanism of nonmutational regulation of gene function mediated by means of short noncoding RNA (Kovalchuk et al, 2008). MicroRNAs (miRNAs) are a class of short (~22 nucleotide), single-stranded non-coding RNAs that usually bind their target mRNAs through imperfect base pairing in Qing Hu 1& , Jian-Ping Gong 1& , Jian Li 1 , Shan-Liang Zhong 2 , Wei-Xian Chen 1 , Jun-Ying Zhang 1 , Teng-Fei Ma 2 , Hao Ji 1 , Meng-Meng Lv 1 , Jian-Hua Zhao 2 *, Jin-Hai Tang 1 * the 3'-untranslated regions (3' UTRs) and impact protein expression by translational repression, mRNA degradation or the promotion of mRNA decay (Kutanzi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It will be interesting to verify if the same phenomenon is also observed in patient tumor samples. The regulation of the other two major multidrug resistance transporters, Pglycoprotein/MDR1 and MRP1, by miR-451, -27a and -326, respectively, have also been reported (Kovalchuk et al, 2008;Liang et al, 2010). More importantly, modulation of miRNA expression or function can alter sensitivity of cancer cells to anticancer drugs (Zhu et al, 2008;Pan et al, 2009;Blower et al, 2008).…”
Section: Microrna-mediated Regulation Of Abcg2mentioning
confidence: 98%
“…This transfer resulted in the acquisition, by the recipient cells, of the drug resistant characteristics of the donor cells. 153,160,161 In a recent study, the authors analysed the molecular basis for the acquired traits, looking for some miRs which had previously been reported 73,106,129,130,144 (and described above) as enhancers of P-gp expression in drug resistant cancer cells (miR-27a and miR-451). They demonstrated that the transfer of transcripts and miRs through microvesicles plays an important role in conferring MDR by "retemplating" recipient cells in order to reflect the donor cell (P-gp overexpressed) phenotype.…”
Section: P-gp and The Micrornas Involved In Its Regulation May Be Prementioning
confidence: 99%